Exploring Gender Based Challenges Faced By Female Healthcare Professionals - Eman Sarwar; Sania Arshad; Rameen Rehman; Sana Arshad (Cleanliness: Journal of Health Sciences and Medical Research, 2026)
Female healthcare professionals continue to face gender-based challenges. These issues not only affect their professional growth and well-being but also have broader implications for healthcare quality and workforce sustainability. The present qualitative study aimed to explore gender-based challenges faced by female healthcare professionals in Pakistan and their impact on career progression and workplace experiences. A purposive sample of seven female healthcare professionals aged 25–40 years, working in various healthcare settings including hospitals and private clinics, was selected. Data was collected through face-to-face, semi-structured interviews. The interviews were transcribed and analyzed using thematic analysis, involving line-by-line coding followed by the development of themes. Findings revealed five major themes: uncomfortable workplace environment, injustice, gender inequality, male dominancy, and overcompensation. The study concludes that gender-based challenges significantly affect the professional experiences and career progression of female healthcare professionals in Pakistan. Addressing these issues through organizational policies and gender equity initiatives is essential to create a supportive and inclusive work environment.